The Magician's Nephew : The Chronicles of Narnia - Lewis, C. S. (Lahore ILQA Publications, 2015)
On a daring quest to save a life, two friends are hurled into another world, where an evil sorceress seeks to enslave them. But then the lion Aslan's song weaves itself into the fabric of a new land, a land that will be known as Narnia. And in Narnia, all things are possible. This hardback edition of The Magician's Nephew, book one in the classic series, The Chronicles of Narnia, is complete with cover and colour interior art by the original illustrator, Pauline Baynes
Keywords: Narnia (Imaginary place) -- Fantasy -- England